Educação e questão social: o pensamento freiriano na pedagogia do oprimido - Marques, Paulo Roberto Firmino (2021)
The present research seeks to understand the historical and philosophical foundations of Paulo Freire's theoretical constructions in his Pedagogy of the Oppressed, which attempted to account for the manifestations of the "social question" with which the educator confronted in his political-professional work in Latin America in the 1960s. This study is justified as it contributes to the debate about Freirian thought through a direct dialogue with the academic production of Brazilian Social Service. I created the category "oppressed social insertion" to describe the concrete situation, which Freire confronted in Brazil and Chile. This category aims at denoting the set of material and immaterial factors that reproduce situations of oppression for the descendants of indigenous and African populations in the South of the American continent. The critical reading of the Pedagogy of the Oppressed was made with the support of historiographically inspired documental research, complemented by bibliographical research about the historical period treated. The hypotheses formulated try to demonstrate that Freire's book, beyond a classic of educational thought, is a work that directly dialogues with the daily life of the Chilean agrarian reform, with the Left thinking in the 1960s, and is opposed to American imperialism